Frankopan, Peter. The New Silk Roads: The Present and Future of the World, London: Bloomsbury, 2019, 368 pp. - Akyildiz, Sevket (Cappadocia Journal of Area Studies, 2022)
Book review: Frankopan, Peter. The New Silk Roads: The Present and Future of the World, London: Bloomsbury, 2019, 368 pp.